A study of the binary marginal effect of technical barriers to trade on the export of shellfish and aquatic products in China - Xiaoming Chen; Xin Shan; Peng Xin; Jian Xu (PLoS ONE, 2025)
This study aims to examine the impact of technical barriers to trade (TBT) on China’s shellfish exports, focusing on both the intensive margin (trade volume) and the extensive margin (trade type). The research includes shellfish and aquatic products such as scallops, mussels, clams, oysters, and abalone, using HS-6 codes from 2003 to 2020. Panel data is employed for analysis. The findings reveal that TBT notifications positively influence the extensive margin by increasing export types but have a less significant effect on the intensive margin. Economic scale, variable trade cost, and productivity level affect both margins. To mitigate the effects of TBT, China should diversify its shellfish exports. Additionally, reducing trade costs can further enhance China’s shellfish export competitiveness.